Diagnosis dan Tata Laksana Perdarahan Batang Otak Primer - Henry Hadianto (Cermin Dunia Kedokteran, 2024)
Primary brainstem hemorrhage is an intracerebral hemorrhage that affects the brainstem, primarily caused by chronic hypertension. Clinical manifestations include decreased consciousness, motor weakness, respiratory problems, hyperthermia, and pupillary abnormalities. Diagnosis is with a head CT scan/MRI, bleeding was found in the mesencephalon, pontine, or medulla oblongata. Management is conservative with stabilization of vital signs, correction of hemostatic abnormalities, and intensive monitoring of neurological symptoms. Surgery is still controversial because of the lack of clinical and research evidence. The prognosis is generally grave depending on the degree of initial loss of consciousness, location, and volume of bleeding.